Analysis of the Effectiveness of Customer Fraud Reporting Services Through Web-Based Fund Transfers at BRI Ponorogo Branch - Putra, Achmad Nowenta; Cikusin, Yaqub; Ahmadi, Rulam; Muchsin, Slamet; Anadi, Yandri Radhi (Faculty of Law, Universitas Pekalongan, 2024)
This study analyzes the effectiveness of customer fraud reporting services through a web-based fund transfer system at BRI Ponorogo Branch. Using qualitative methods, this study collects data through in-depth interviews, participatory observations, and document analysis to evaluate ease of use, speed of response, and customer satisfaction as well as challenges faced by bank officers. The findings show that the web-based system is effective in speeding up the handling of reports and increasing customer satisfaction, with responses generally received in less than 24 hours. Customers find this system easy to use and useful, despite technical obstacles and limited access to data faced by officers. Professional interaction between bank officers and customers also contributes to high satisfaction. Analysis of the documentation shows an increase in the number of fraud reports handled since the implementation of this system. Recommendations to improve effectiveness include increased training for bank officers, improvements to technological infrastructure, and the development of additional features on the system. This research provides important insights for the development of fraud reporting systems in the banking sector, with the hope of improving customer protection in the future.